Role of Government and Non-Governmental Organisations (NGOs) in Cyclone Recovery in Bangladesh - Shahpara Nawaz; Md. Humayain Kabir; Md. Nazmul Hossen (TDMRC, Universitas Syiah Kuala, 2022)
Immediate relief distribution activities are primarily focused on after a cyclonic event in Bangladesh, where proper long-term recovery and rehabilitation efforts are not strategized with much significance. This study concentrated on understanding and assessing the status and effectiveness of the post-cyclone recovery programmes to improve the lives of cyclone-affected households in southwestern Bangladesh. This study aims to examine the status and efficiency of Government and Non-government organisations (NGO) led cyclone recovery programmes for cyclone SIDR and cyclone AILA and identify the challenges that hindered the successful implementation of effective recovery programmes. The study reviewed existing literature on cyclone recovery in Bangladesh, including government and NGO reports, and conducted focus group discussions on cyclone-affected Dacope Upazila of Khulna. The finding indicates that the cyclone-affected community in southwestern Bangladesh has not recovered satisfactorily across all sectors and timescales from cyclone damages and continues to live in vulnerable conditions even after a decade of cyclonic events. The adopted recovery measures were not efficient and effective in returning to the everyday lifestyle of the affected people. Planned and coordinated recovery efforts should be executed with proper monitoring to ensure the effectiveness of post-cyclone recovery programmes.